2007
DOI: 10.2114/jpa2.26.113
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Light-induced Suppression of Nocturnal Melatonin with Special Reference to Variations in the Pupillary Light Reflex in Humans

Abstract: The purpose of the present study was to elucidate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…In a previous study by Yasukouchi et al, there was no linear relationship between the PLR and melatonin suppression levels (in response to different light intensities, ranging from 1-30 lux for the PLR, and from 30-600 lux for melatonin suppression). 35 We also did not find any significant association between baseline dim light pupil size and salivary melatonin concentrations.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In a previous study by Yasukouchi et al, there was no linear relationship between the PLR and melatonin suppression levels (in response to different light intensities, ranging from 1-30 lux for the PLR, and from 30-600 lux for melatonin suppression). 35 We also did not find any significant association between baseline dim light pupil size and salivary melatonin concentrations.…”
Section: Discussioncontrasting
confidence: 57%
“…32 These and other studies lend support to the notion that there is a circadian modulation of the sensitivity of the nonvisual light photoreception system to light as already has been shown for the visual photoreceptive system. [33][34][35] Given that melanopsin is the primary circadian photoreceptor, we hypothesize that the intrinsic melanopsin-mediated pupil response may show a 24-hour variation that is influenced by the circadian clock and, therefore, will persist under constant dim lighting conditions. In our study, we addressed the question of whether the PLR varies with time of day.…”
mentioning
confidence: 99%
“…The second is that the high potential of melatonin synthesis based on the high serotonin synthesis in the pineal during daytime might be available due to the night exposure to the “low temperature light” emitted from incandescent bulbs. Although many reports have shown that melatonin secretion is suppressed by light emitted from fluorescent lamps including short wave length (with around 460 nm of wave length) components [25-27], and especially short wave length light [27-30], this study newly implies that the combined behaviors of modifying breakfast content, receiving sunlight exposure and receiving exposure to low color temperature lighting at night can facilitate achievement of high plasma melatonin at night in humans.…”
Section: Discussionmentioning
confidence: 86%
“…The second component is that the high potential of melatonin synthesis based on the high serotonin synthesis in the pineal during daytime might be available due to the night exposure to the "low-temperature light" emitted from incandescent bulbs. Many reports have shown that melatonin secretion is suppressed by evening or night light emitted from fluorescent lamps including shortwave length (with around 460 nm of wave length) components [10,33,35,[54][55][56]. Moreover, this study newly implies that the combined behaviors of (1) modifying breakfast content, (2) receiving sunlight exposure, and (3) receiving exposure to low color temperature lighting at night can facilitate achievement of high plasma melatonin at night in humans.…”
Section: Discussionmentioning
confidence: 62%